Development of a Decision Assisting Soil Information System in Agriculture - Dorka, Dénes (Acta Agraria Debreceniensis, 2004)
Hungarian agriculture may be characterized by the industry-like, conventional farming of the past decades. This form of management concentrated exclusively on functions aimed at production. We have to decrease this disproportion, especially when joining to the EU, by reducing the intensive agricultural regions and adjusting to the goals of the 2000-2006 NAEP programmes, forming such an agricultural system which integrates the advantages of both environmental protection and complex agricultural systems based on rational foundations. Nevertheless it’s a rational decision to make the soil information system with an exact spatial informatics background as a foundation of agricultural system, because this promotes easy handling as well the connection to possible subsequent modules.